2018
DOI: 10.1103/physrevlett.120.107202
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Magnetization Control by Symmetry Breaking of Photoinduced Spin Reorientation with Intense Terahertz Magnetic Near Field

Abstract: We exploit an intense terahertz magnetic near field combined with femtosecond laser excitation to break the symmetry of photoinduced spin reorientation paths in ErFeO_{3}. We succeed in aligning macroscopic magnetization reaching up to 80% of total magnetization in the sample to selectable orientations by adjusting the time delay between terahertz and optical pump pulses. The spin dynamics are well reproduced by equations of motion, including time-dependent magnetic potential. We show that the direction of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Furthermore, the coherent control of the magnetization states at a macroscopic level in the weak ferromagnetic ErFeO 3 was experimentally achieved for the first time through the use of magnetic metamaterials and optical pulses. [316] The researchers succeeded in aligning the macroscopic magnetization up to 80% of the total magnetization to selectable orientations by adjusting the arrival timing between the THz and optical pump pulses. To obtain sufficient precession amplitude in the first stage, the THz magnetic field in the near-field region was enhanced using metamaterials.…”
Section: Spin State Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the coherent control of the magnetization states at a macroscopic level in the weak ferromagnetic ErFeO 3 was experimentally achieved for the first time through the use of magnetic metamaterials and optical pulses. [316] The researchers succeeded in aligning the macroscopic magnetization up to 80% of the total magnetization to selectable orientations by adjusting the arrival timing between the THz and optical pump pulses. To obtain sufficient precession amplitude in the first stage, the THz magnetic field in the near-field region was enhanced using metamaterials.…”
Section: Spin State Controlmentioning
confidence: 99%
“…Copyright 2017, American Physical Society. c) Reproduced with permission [316]. Copyright 2018, American Physical Society.…”
mentioning
confidence: 99%
“…Many other materials showing dynamic THz responses applicable to active THz modulation also exist, such as NbO 2 , [211] InSb, [212,213] QWs, [214] titanium oxides, [215] orthoferrites, [216][217][218] rare-earth nickelates, [219][220][221] manganites, [222][223][224] topological insulators, [225][226][227] multiferroics, [228] molecular crystals, [229,230] medicines, [231] polymers, [232][233][234][235][236][237][238] and halide perovskites, [239][240][241][242][243][244][245][246] to name but a few. Considering the diversity of the material properties and the control mechanisms, plasmonic hybridization may bring about new possibilities for a wide variety of active THz devices.…”
Section: Potential Candidatesmentioning
confidence: 99%
“…The right side shows the dominant process of symmetry destruction in the terahertz magnetic field. The magnetization tilt is caused by the free spin precession and non-resonant field excitation forced oscillation [188], copyright American Physical Society, 2018.…”
Section: Figurementioning
confidence: 99%
“…A strong THz magnetic field can cause a large magnetization change of 40%, and the change in magnetization can remain sufficiently large to cause a redshift even after the magnetic field disappeared. Kurihara et al demonstrated a combination of the terahertz magnetic field of the SRR and femtosecond laser excitation to break the symmetry of the light-induced spin reorientation path in ErFeO 3 [188]. By controlling the arrival time of the optical and terahertz pump pulses, the final state reaches more than 80% of the total magnetization in the optional direction.…”
Section: Spintronics Metasurfacementioning
confidence: 99%